Penile cancer: Providing patient support. Issue 4 (April 2018) - Pullen, Richard L.
Abstract : Men diagnosed with penile cancer are likely to have questions and concerns about their diagnosis and treatment, sexual function, and masculine identity. This article discusses the types of penile cancer, reviews current treatment approaches, and offers practical guidelines for patient teaching and psychosocial support.